Associations between otitis media and child behavioural and learning difficulties: Results from a Danish cohort. (May 2016) - Niclasen, J.; Obel, C.; Homøe, P.; Kørvel-Hanquist, A.; Dammeyer, J.
Abstract: Objectives: Findings from studies investigating early childhood episodes of otitis media (OM) and developmental outcomes are inconclusive. This may in part be because large-scale prospective studies controlling for relevant confounding factors are sparse. The present study investigates associations between OM in early childhood and later behavioural and learning difficulties controlling for relevant confounding factors. Methods: The study applied data from the Aarhus Birth Cohort's 10–12-year-old follow-up ( N  = 7578). Associations between retrospective parent-reported OM (no OM; 1–3 episodes of OM with/without tympanostomy tubes; 4+ OM episodes without tympanostomy tubes and; 4+ OM episodes with tympanostomy tubes) one the one hand, and parent- and teacher-reported scores on the Strengths and Difficulties Questionnaire (SDQ) and parent-reported academic difficulties on the other hand, were investigated. The following variables were controlled for: parental educational level, maternal and paternal school problems, parental post-natal smoking, breastfeeding, and age at which the child started walking. All analyses were stratified by gender. Results: Large differences in background characteristics were observed for the group of children with 4+ OM episodes with tympanostomy tubes compared to the no OM group. After controlling for relevant confounders, negative associations were consistently observed for the group of children with 4+ episodes of OM with tympanostomy tubes compared to the group of children without OM. This was particularly so for girls. Conclusion: The findings suggest an association between 4+ episodes of early OM with tympanostomy tubes and behavioural and learning difficulties later in childhood. The large inter-group differences, i.e. impact of residual and unmeasured confounding factors, may in part explain the observed associations and underline the need to include these in future studies.